Healthcare management and leadership roles - Lopes da Costa, R.; Pereira, L.; Gonçalves, R.; Dias, Á.; Jerónimo, C. H.; Teixeira, N. (International Journal of Electronic Healthcare, 2022)
Within the changes in healthcare system across the years, new challenges emerge for healthcare practitioners, organisations, and their management boards, so the recognition of the need for different health professionals in healthcare management has been growing. However, physiotherapists' core responsibilities remain rooted on therapeutic practices and rehabilitation, developed primarily in clinical and hospital environments. Regarding this scenario, physiotherapists' functions continue to be absent to the highest healthcare management and leadership positions, despite their knowledge and understanding about how to ensure the best services to the patients. As such, this research aimed to deepen the barriers to physiotherapists' involvement in healthcare management and leadership roles. For such, a cross-sectional survey was performed with 287 physiotherapists, carrying out quantitative and qualitative data collection. Findings suggest that a lack of training and existent policies and laws are evident barriers to the access of both healthcare management and leadership positions.